Pengaruh Gaya Belajar Auditori terhadap Pemahaman Pembelajaran Al-Qur’an di TPQ Mambaul Ulum Desa Dagan Lamongan - Alya Khoironi Muhibbah; Dini Maulidhah; Faziadatun Ni’mah; Feni Tamimul Ummah; Mayaly Maghfiroh; Shofwatul Fikriyyah; Vika Madinatul Ilmi; Eny Lathifah (Universitas Maritim AMNI Semarang, 2024)
The purpose of this study was to determine whether there is an effect of auditory learning style on the understanding of learning the Qur'an in 5th grade students of Madrasah Ibtida'iyah at the Mambaul Ulum al-Qur'an Education Park in Dagan Village. This study uses Quantitative methods with the type of case study through the management of instruments in the form of questionnaires, interviews, observations and documentation and a sample of 48 of the 5th grade students. The results showed that there was no effect of auditory learning style on understanding al-Qur'an learning by an average of 20.03% from variable X (Auditory Learning Style) to variable Y (Understanding al-Qur'an Learning).